Factors Influencing Mathematics Learning in Students in the Alor Islands Region - Adrianingsih, Narita Y.; Sari, Nilam N.; Padafani, Lekison; Mukhti, Tessy Octavia (Mosharafa: Jurnal Pendidikan Matematika, 2024)
Mathematics is a fundamental skill for all individuals, making it essential for every child to achieve proficiency. Several factors influence mathematics learning achievement, which can be categorized into internal and external factors. This study aims to identify the factors affecting mathematics achievement among junior high school students in the Teluk Mutiara District of Alor. The research employed a multiple linear regression analysis method. Data were collected through questionnaires completed by 7th-grade students from junior high schools in the district. The results indicated that factors such as the mother's educational background, the father's occupation, the amount of time allocated for studying mathematics, and the students' interest in learning mathematics significantly influenced their mathematics achievement. Matematika sangat penting bagi setiap orang, oleh karena itu setiap anak harus menguasai matematika. Dalam pembelajaran matematika, terdapat beberapa faktor yang mempengaruhi prestasi belajar matematika yaitu faktor internal dan faktor eksternal. Penelitian ini bertujuan untuk mengetahui faktor-faktor apa saja yang mempengaruhi prestasi belajar matematika pada siswa SMP di Kecamatan Teluk Mutiara Alor. Penelitian ini menggunakan metode analisis regresi linier berganda. Metode pengumpulan data yang digunakan adalah dengan cara mengisi angket yang diisi oleh siswa SMP di Kecamatan Teluk Mutiara. Subjek penelitian adalah anak SMP kelas 7 di Kecamatan Teluk Mutiara Alor. Hasil penelitian menunjukkan bahwa faktor-faktor yang mempengaruhi prestasi belajar matematika pada siswa SMP di Kecamatan Teluk Mutiara Alor adalah pendidikan ibu, pekerjaan ayah, waktu belajar matematika, dan minat belajar matematika.